ALEVIN - A Framework to Develop, Compare, and Analyze Virtual Network Embedding Algorithms - Fischer, Andreas; Botero, Juan; Duelli, Michael; Schlosser, Daniel; Hesselbach, Xavier; De Meer, Hermann (Electronic Communications of the EASST, 2011)
Network virtualization is recognized as an enabling technology for the Future Internet. Applying virtualization of network resources leads to the problem of mapping virtual resources to physical resources, known as “Virtual Network Embedding” (VNE). Several algorithms attempting to solve this problem have been discussed in the literature, so far. However, comparison of VNE algorithms is hard, as each algorithm focuses on different criteria. To that end, we introduce a framework to compare different algorithms according to a set of metrics, which allow to evaluate the algorithms and compute their results on a given scenario for arbitrary parameters.